Acidogenic Potential of Oral Bifidobacterium and Its High Fluoride Tolerance - Manome, Ayumi; Abiko, Yuki; Kawashima, Junko; Washio, Jumpei; Fukumoto, Satoshi; Takahashi, Nobuhiro (Frontiers in Microbiology, 2019)
Bifidobacterium is frequently detected in early childhood caries and white spot lesions, indicating that it is a novel caries-associated bacterium. Bifidobacterium is known to possess a unique metabolic pathway, the “bifid shunt”, which might give it cariogenic potential by increasing its acid production. Thus, we evaluated the acid-producing activity of Bifidobacterium and its sensitivity to fluoride, a caries preventive reagent. B. longum, B. dentium, and Streptococcus mutans were used. Acid-producing activity was measured using a pH-stat in the absence and presence of fluoride under anaerobic conditions. Furthermore, metabolomic analysis was performed to elucidate the mechanism underlying the inhibitory effects of fluoride. The acid production of Bifidobacterium at pH 5.5 was as high as that seen at pH 7.0, indicating that Bifidobacterium has high cariogenic potential, although it produced less acid than S. mutans. In addition, Bifidobacterium produced acid in the absence of extracellular carbohydrates, suggesting that it can store intracellular polysaccharides. Bifidobacterium produced more acid from lactose than from glucose. Bifidobacterium mainly produced acetate, whereas S. mutans mainly produced lactate. The 50% inhibitory concentration (IC50) of fluoride for acid production was 6.0-14.2 times higher in Bifidobacterium than in S. mutans. Fluoride inhibited enolase in the glycolysis, resulting in the intracellular accumulation of 3-phosphoenolpyruvate, glucose 6-phosphate, and erythrose 4-phosphate. However, the bifid shunt provides a bypass pathway that can be used to produce acetate, suggesting that Bifidobacterium is able to metabolize carbohydrates in the presence of fluoride. It is suggested that its exclusive acetate production contributes to the pathogenesis of dental caries.